Cholecystectomy in Sweden 2000 – 2003: a nationwide study on procedures, patient characteristics, and mortality - Stenlund Hans; Nordin Pär; Haapamäki Markku M; Rosenmüller Mats; Nilsson Erik (BMC Gastroenterology, 2007)
Abstract Background Epidemiological data on characteristics of patients undergoing open or laparoscopic cholecystectomy are limited. In this register study we examined characteristics and mortality of patients who underwent cholecystectomy during hospital stay in Sweden 2000 – 2003. Methods Hospital discharge and death certificate data were linked for all patients undergoing cholecystectomy in Sweden from January 1st 2000 through December 31st 2003. Mortality risk was calculated as standardised mortality ratio (SMR) i.e. observed over expected deaths considering age and gender of the background population. Results During the four years of the study 43072 patients underwent cholecystectomy for benign biliary disease, 31144 (72%) using a laparoscopic technique and 11928 patients (28%) an open procedure (including conversion from laparoscopy). Patients with open cholecystectomy were older than patients with laparoscopic cholecystectomy (59 vs 49 years, p < 0.001), they were more likely to have been admitted to hospital during the year preceding cholecystectomy, and they had more frequently been admitted acutely for cholecystectomy (57% Vs 21%, p < 0.001). The proportion of women was lower in the open cholecystectomy group compared to the laparoscopic group (57% vs 73%, p < 0.001). Hospital stay was 7.9 (8.9) days, mean (SD), for patients with open cholecystectomy and 2.6 (3.3) days for patients with laparoscopic cholecystectomy, p < 0.001. SMR within 90 days of index admission was 3.89 (3.41–4.41) (mean and 95% CI), for patients with open cholecystectomy and 0.73 (0.52–1.01) for patients with laparoscopic cholecystectomy. During this period biliary disease accounted for one third of all deaths in both groups. From 91 to 365 days after index admission, SMR for patients in the open group was 1.01 (0.87–1.16) and for patients in the laparoscopic group 0.56 (0.44–0.69). Conclusion Laparoscopic cholecystectomy is performed on patients having a lower mortality risk than the general Swedish population. Patients with open cholecystectomy are more sick than patients with laparoscopic cholecystectomy, and they have a mortality risk within 90 days of admission for cholecystectomy, which is four times that of the general population. Further efforts to reduce surgical trauma in open biliary surgery are motivated.